Browsing through sealed historical manuscripts by using 3-D computed tomography with low-brilliance X-ray sources. Issue 1 (December 2018) - Stromer, Daniel; Christlein, Vincent; Martindale, Christine; Zippert, Patrick; Haltenberger, Eric; Hausotte, Tino; Maier, Andreas
Abstract Severely damaged historical documents are extremely fragile. In many cases, their secrets remain concealed beneath their cover. Recently, non-invasive digitization approaches based on 3-D scanning have demonstrated the ability to recover single pages or letters without the need to open the manuscripts. This can even be achieved using conventional micro-CTs without the need for synchrotron hardware. However, not all manuscripts may be suited for such techniques due to their material and X-ray properties. In order to recommend which manuscripts and which inks are best suited for such a process, we investigate six inks that were commonly used in ancient times: malachite, three types of iron gall, Tyrian purple, and buckthorn. Image contrast is explored over the complete pipeline, from the X-ray CT scan and page extraction to the virtual flattening of the page image. We demonstrate, that all inks containing metallic particles are visible in the output, a decrease of the X-ray energy enhances the readability, and that the visibility highly depends on the X-ray attenuation of the ink's metallic ingredients and their concentration. Based on these observations, we give recommendations on how to select the appropriate imaging parameters.